2019
DOI: 10.1155/2019/5160293
|View full text |Cite|
|
Sign up to set email alerts
|

WS-5 Extract of Curcuma longa, Chaenomeles sinensis, and Zingiber officinale Contains Anti-AChE Compounds and Improves β-Amyloid-Induced Memory Impairment in Mice

Abstract: Alzheimer's disease (AD) is linked to an extensive neuron loss via accumulation of amyloid-beta (Aβ) as senile plaques associated with reactive astrocytes and microglial activation in the brain. The objective of this study was to assess the therapeutic effect of WS-5 ethanol extract in vitro and in vivo against Aβ-induced AD in mice and to identify the extract’s active constituents. In the present study, WS-5 exerted a significant inhibitory effect on acetylcholinesterase (AChE). Analysis by transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In previous clinical studies, supplementation with anti-inflammatory medicinal herbs improved the scores for GH, VT, MH, and MCS [67,68]. WEC have been found to prevent not only the production of TNF-α and IL-6 in activated brain microglial cells/macrophages, but also neuroinflammation associated with fatigue, depression, and memory impairment in animal studies [20,69,70]. Therefore, it is possible that WEC improved HR-QOL by alleviating inflammation-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In previous clinical studies, supplementation with anti-inflammatory medicinal herbs improved the scores for GH, VT, MH, and MCS [67,68]. WEC have been found to prevent not only the production of TNF-α and IL-6 in activated brain microglial cells/macrophages, but also neuroinflammation associated with fatigue, depression, and memory impairment in animal studies [20,69,70]. Therefore, it is possible that WEC improved HR-QOL by alleviating inflammation-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a systematic review and meta-analysis of 18 clinical trials found an antidepressant effect for minocycline, a suppressor of microglial activation [ 85 ]. In activated microglial cells, C. longa extract, turmeronol A, and turmeronol B were found to inhibit the production of inflammatory mediators, including TNF-α and IL-6 [ 86 , 87 ]. In addition, in animal studies C. longa extract inhibited the neuroinflammation associated with fatigue [ 88 ], depression [ 27 ], memory impairment [ 86 ], and anxiety- and sleep deprivation-induced behavior abnormalities [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…In activated microglial cells, C. longa extract, turmeronol A, and turmeronol B were found to inhibit the production of inflammatory mediators, including TNF-α and IL-6 [ 86 , 87 ]. In addition, in animal studies C. longa extract inhibited the neuroinflammation associated with fatigue [ 88 ], depression [ 27 ], memory impairment [ 86 ], and anxiety- and sleep deprivation-induced behavior abnormalities [ 89 , 90 ]. In the present study, dietary supplementation with CLE improved mental health and negative mood state, suggesting that these improvements could be related in part to inhibition of microglial activation in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence indicates that CUR would exert its effects independently of the Age-1-DAF-16 pathway but rather through other constituents of the IIS pathway. With regard to cognitive impairment, the in vivo experiment demonstrated that CUR can improve learning and memory also reducing Aβ plaque formation in the context of Alzheimer disease (AD) [146]. D. melanogaster is a promising animal model for research in AD [147].…”
Section: Study Of Longevity In Drosophila Melanogaster Andmentioning
confidence: 99%